Can Mimicking Infants' Early Experience Facilitate Adult Learning? A Critique of Hudson Kam (2017). Issue 4 (2nd October 2018) - Arnon, Inbal
ABSTRACT: Why do adults seem to struggle more than children in learning a second language, despite being better at a range of other cognitive skills? The source of L1-L2 differences in language learning is one of the most debated topics in the study of language. One hypothesis is that L1-L2 differences are primarily experience-based, with language learning abilities themselves showing a high degree of plasticity. Hudson-Kam (2018) recently presented findings that seem to go against this hypothesis: in five studies, adults failed to show better learning in a more infant-like environment. In this article, I offer a theoretical and empirical critique of these findings and outline some open questions for investigating experience-based explanations for L1-L2 differences. In short, the main critique has to do with how we define what infant-like (or child-like) learning is and how we identify which aspects of children's experience facilitate which aspects of language learning.